PERAN MASYARAKAT DALAM PENGELOLAAN SAMPAH RUMAH TANGGA - Putra Abrianto, Andika Bimantara; Indraswari, Citra Rahayu (Journal of Development Economic and Social Studies, 2024)
Waste is the most common thing discussed in every community, especially how to manage it. With the large population of the world community, more and more waste is generated around the environment which will cause pollution. The problem that can be taken is how the community manages household waste. The method used is a descriptive qualitative method, which is the main focus in the community that manages household waste and how to overcome it in the future.